Inter-Orthodox controversies between Romania and Yugoslavia in the interwar period - Brusanowski, Paul (HTS teologiese studies, 2021)
This article examines the disputes that existed in the interwar period over the recognition of a Romanian Orthodox bishopric in Yugoslavia (The official name ‘Yugoslavia’ was only adopted in 1929. From 1918 to 1929, the state was officially called the Serbo-Croatian-Slovenian Kingdom. For the sake of simplicity, I will use the name Yugoslavia throughout this article.) and a Serbian Orthodox bishopric in Romania. The reason for this was the existence of two ethnically distinct Orthodox Churches (Serbian and Romanian) on the territory of the dualistic Hungarian monarchy before 1918, but both with de facto autocephalous status and territorial overlap. They came into being after the decision of the Synod of Bishops of the Hungarian Orthodox Metropolis to separate the existing parishes and dioceses along ethnic lines. After the break-up of the dualistic monarchy at the end of the First World War, one of the Serbian Orthodox dioceses landed on the territory of Yugoslavia (Vršac) and the second on the territory of Romania (Timișoara). However, both Romanian bishoprics (Arad and Caransebeș) ended up in Romania. Under these circumstances, several Romanian parishes in the Yugoslav Banat remained without a direct episcopal hierarchy. As a result, diplomatic negotiations began between the Romanian and Yugoslav governments and between the hierarchs of the Orthodox Churches of Romania and Yugoslavia on the establishment of a Romanian diocese on Yugoslav territory.Contribution: This article deals with a lesser-known topic on the history of the Orthodox Churches in South Eastern Europe. Because there is no extensive literature on this subject, I have made use of unpublished documents from the archives of the Metropolitanate of Sibiu (Transylvania, Romania).